(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2024)
This comprehensive descriptive research explores deeply into the intricate domain of new product development within Nepal’s Chitwan district, examining its complicated process, stages, evolving trends, and consequential implications. With a robust participant pool of Four hundred and Four (N=404) individuals spanning diverse manufacturing and service-oriented entities, the study provides a panoramic view of the subject matter. The findings reveal a substantial consensus (85.9%) among respondents, declaring the significance of stages, trends, and strategies in new product development, underscoring their pervasive acknowledgement across the district. However, a notable subset (25%) displays partial implementation, particularly regarding concept development and testing, reflecting challenges in translating design phases into seamless product launches and market integration. Yet, a considerable segment (80.6%) displays alignment with product life cycles, new product development stages, trends, and strategies, signalling adaptability and steadfast commitment among Chitwan’s enterprises. With an average knowledge score of 5.38 out of 8, the research augments the requirements of theoretical knowledge to the decision makers. These insights resonate especially in urban settings, elucidating the interplay between new product development trends and their far-reaching implications for business competitiveness, consumer experiences, and societal advancement.